2012
DOI: 10.1002/anie.201203920
|View full text |Cite
|
Sign up to set email alerts
|

An Amphiphilic Dendrimer for Effective Delivery of Small Interfering RNA and Gene Silencing In Vitro and In Vivo

Abstract: An amphiphilic dendrimer bearing a hydrophobic alkyl chain and hydrophilic poly(amidoamine) dendrons is able to combine the advantageous features of lipid and dendrimer vectors to deliver a heat shock protein 27 siRNA and produce potent gene silencing and anticancer activity in vitro and in vivo in a prostate cancer model. This dendrimer can be used alternatively for treating various diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
226
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 230 publications
(233 citation statements)
references
References 32 publications
(27 reference statements)
5
226
1
Order By: Relevance
“…17 They have been investigated for biomedical applications as nanocarriers for hydrophobic drug molecules, gene therapy etc. [18][19][20][21][22][23][24][25][26][27] However, studies on parameters which influence their self-assembly have not been attempted very much. In general, there are several factors that govern the self-assembly of amphiphiles, for example, hydrophilic-lipophilic balance (HLB), choice of solvent, etc.…”
mentioning
confidence: 99%
“…17 They have been investigated for biomedical applications as nanocarriers for hydrophobic drug molecules, gene therapy etc. [18][19][20][21][22][23][24][25][26][27] However, studies on parameters which influence their self-assembly have not been attempted very much. In general, there are several factors that govern the self-assembly of amphiphiles, for example, hydrophilic-lipophilic balance (HLB), choice of solvent, etc.…”
mentioning
confidence: 99%
“…The N/P ratio = 1 needed for efficient DNA compaction is expected to render this new aminofullerene a transfection agent with minimum side effects. 28 Finally, the modular synthetic strategy will provide easy access to a variety of derivatives that are useful for targeting biomolecules such as RNA 29 and proteins. 13,30 This work was supported by KAKENHI (No.…”
Section: ¹1mentioning
confidence: 99%
“…[9][10][11] Recent studies on dendrons carrying a lipid tail have shown that they hold great promise as non-viral transfectants for genetic materials such as siRNA. [12][13][14] Hence, the ability to form selfassembled structures may be an important feature when applying dendrimers as carriers for drugs and genes.…”
Section: Introductionmentioning
confidence: 99%